Healing Rates and Functional Outcomes After Triple-Loaded Single-Row Versus Transosseous-Equivalent Double-Row Rotator Cuff Tendon Repair - Tashjian, Robert Z. (Orthop J Sports Med, 2018)
BACKGROUND: Although healing rates and outcomes of arthroscopic single-row rotator cuff repairs have been compared with double-row repairs, none have utilized triple-loaded anchors. PURPOSE: To compare healing and function after single-row repairs with triple-loaded anchors versus double-row repairs with a suture-bridge technique. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: A single surgeon performed arthroscopic rotator cuff repair on 47 consecutive patients with an easily reducible full-thickness rotator cuff tear of medium size (1-3 cm). A retrospective cohort study was performed in which the first 25 patients underwent repair with a double-row suture-bridge (DRSB) technique. The next 22 patients underwent repair with a single-row technique with triple-loaded anchors and simple stitches (SRTL) after a change in technique by the surgeon. Twenty-one DRSB and 18 SRTL repairs were evaluated preoperatively and at a minimum of 12 months postoperatively with a visual analog scale for pain, the American Shoulder and Elbow Surgeons form, and the Simple Shoulder Test. Healing was evaluated with magnetic resonance imaging at a minimum of 12 months. RESULTS: When DRSB repairs were compared with SRTL repairs, there were no significant differences in patient age (61 vs 65 years), tear size (2.3 vs 2.1 in the sagittal plane; 2.0 vs 1.8 cm in the coronal plane), Goutallier fatty infiltration (supraspinatus grade: stage 0, 38%; stage 1, 38%; stage 2, 19%; stage 3, 5%; vs stage 0, 56%; stage 1, 39%; stage 2, 5%; stage 3, 0%), tendon healing (71% vs 78%), improvement in visual analog scale pain score (3.7 vs 3.2), or improvement in American Shoulder and Elbow Surgeons scores (34.6 vs 36.9), with P > .05 in all cases. SRTL repairs had significantly greater improvement in Simple Shoulder Test scores versus DRSB repairs (6.6 vs 4.5; P = .03). CONCLUSION: DRSB and SRTL repairs have similar improvements in pain and function with equivalent healing rates for arthroscopic repair of mobile full-thickness rotator cuff tears of medium size (1-3 cm).